Spontaneous rupture of nontraumatic hepatic artery pseudoaneurysm. Issue 4 (22nd April 2023) - Boyd-Tressler, Andrea; Follette, Craig; Oechsel, Kelly; Carmichael, Samuel; Stettler, Gregory R; Avery, Martin
Abstract: Spontaneous rupture of hepatic artery pseudoaneurysms (HAP) is a rare cause of intra-abdominal hemorrhage. Herein, we present a case of a spontaneous rupture of a nontraumatic HAP. A 61-year-old female, not on any anticoagulant or antiplatelet medications, presented with abdominal pain and hemorrhagic shock. Cross-sectional imaging revealed a left HAP with evidence of active bleeding. Emergent diagnostic angiography was performed, and angioembolization of an actively bleeding pseudoaneurysm was performed. Given the risk of rupture and high mortality rate associated with rupture, aggressive treatment of HAP should be pursued.